The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s10660-009-9033-5
|View full text |Cite
|
Sign up to set email alerts
|

E-auction web assessment model in China

Abstract: Electronic auction (e-auction), a major e-commerce model, has enjoyed rapid growth in many countries. This study develops a web assessment model (EAWAM) from a consumer perspective that suggests that user intention to continue using an e-auction website is based on users' satisfaction with the e-auction website, which is determined by perceived e-auction user friendliness, functionality and interactivity. Web trustworthiness serves as an important antecedent to perceived e-auction user friendliness and functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…On another note, user satisfaction is another concept that has been widely acknowledged as a surrogate measure of system success in the field of Information Systems (IS) and as a predictor of customer loyalty and retention in the Marketing disciplines (Lu et al, 2009; Wu and Wang, 2006). We define user satisfaction as users’ overall evaluation of service experiences after the actual use of the service over time (Garbarino and Johnson, 1999).…”
Section: Development Of Conceptual Framework and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…On another note, user satisfaction is another concept that has been widely acknowledged as a surrogate measure of system success in the field of Information Systems (IS) and as a predictor of customer loyalty and retention in the Marketing disciplines (Lu et al, 2009; Wu and Wang, 2006). We define user satisfaction as users’ overall evaluation of service experiences after the actual use of the service over time (Garbarino and Johnson, 1999).…”
Section: Development Of Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…It is a crucial variable to be investigated when aiming to predict post-adoption behavioral variables, particularly because it can be measured only after an actual experience of technology or service use (Rogers, 2010). Furthermore, previous studies have confirmed the positive relationship between user satisfaction and actual use (Lu et al, 2009); therefore, we include user satisfaction in our conceptual framework.…”
Section: Development Of Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…Website characteristics influence and are influenced by the other factors proposed here. For example, Lu and colleagues [5] proposed that trustworthiness leads to consumers' higher evaluation of an e-auction site's friendliness, functionality and interactivity. Secondly, the knowledge gap should be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the following papers in current literature, there is not any country-level decision making model to assess the current status of e-Commerce maturity in countries: US [30]; UK [31]; Brazil [32]; Mexico [33]; in Greece [34]; South Korea [35]; Singapore [36][37][38]; Hong Kong [39]; China [40][41][42][43]; India [44]; Malaysia [45,46]; developing countries [47] and global e-Commerce researches [48][49][50][51][52] For this purpose, we present a three-level national e-Commerce self-assessment framework where: 1) it addresses the gaps in the effective self-assessment of country-level e-Commerce maturity; 2) it considers three levels of local, regional, international e-Markets along with interdependencies between them in the national e-Commerce self-assessment process; 3) it synthesizes qualitative judgments and quantitative data of maturity criteria and sub-criteria; and 4) it considers fuzzy logic and fuzzy sets to represent ambiguous, uncertain or imprecise information. The results of this e-Commerce maturity self-assessment allow a country to discern clearly its strengths and areas in which improvements can be made and culminate in planned improvement actions that are then monitored for progress.…”
Section: Introductionmentioning
confidence: 99%